ANALYSIS OF TRANSCRIPTS AND CARDIAC MYOSIN-BINDING PROTEIN WITH VARIANTS OF UNCERTAIN SIGNIFICANCE IN CARDIOMYOCYTES - Guterres, Egas Manuel; Guterres, Luis Manuel (Folia Medica Indonesiana, 2025)
Mutations in the myosin-binding protein C (MYBPC3) gene, particularly variants of uncertain significance (VUS), are associated with cardiomyopathies. This systematic review aims to analyze the impact of VUS mutations in MYBPC3 on transcripts and proteins in cardiomyocytes. A comprehensive literature search across multiple databases (i.e., PubMed, Google Scholar, and ScienceDirect) identified relevant studies focusing on the effects of these mutations on transcript and protein levels. Additionally, exclusion criteria were applied, and studies were excluded if they did not focus on cases analyzing transcript levels and MYBPC3 protein behavior in cardiomyocytes harboring VUS mutations. A total of fifteen studies published between 2015 and 2023 were selected after undergoing rigorous screening and quality assessment processes. Data extraction and quality assessment were conducted using standardized tools. This review highlights the diverse impacts of VUS mutations on MYBPC3 transcript expression and protein function, utilizing common methodologies such as next-generation sequencing (NGS), quantitative polymerase chain reaction (qPCR), western blotting, and immunofluorescence. VUS mutations can lead to altered transcript levels and disruptions in protein localization and stability, contributing to the pathogenesis of cardiomyopathies. This study underscores the need for further functional studies to gain a deeper understanding of the role of MYBPC3 VUS mutations in cardiac pathology and to enhance their clinical interpretation.